Chmury piętra wysokiego, średniego i niskiego: analiza zachmurzenia w Polsce - Grajek, Zofia; Dyszy, Wiktoria (Badania Fizjograficzne Seria A - Geografia Fizyczna, 2023)
The subject of the paper is an analysis of the type of clouds in Poland in 1996–2020 on the low, middle and high levels. Daily data on cloud types and the cloudiness of the low-level from 36 IMWM-NRI stations were used. In the analysed multi-year period, the highest share of low-level clouds was observed (56%), followed by mid-level clouds (23%), and the lowest share of high-level clouds (21%). There was a slight decrease in the share of low-level clouds, and an increase in the share of middle and high levels clouds in the analysed period. The share of low-level clouds was highest in the cool season and during the afternoon and night hours; it was lowest in the summer, and early morning and evening hours. The middle and high levels had the highest share in the summer and during the early evening and early morning hours. These levels were least frequent in the winter, and around noon for the mid-level, and at night for the high-level. The Cumulus humilis and Stratocumulus cugen clouds were most frequently observed on the low-level during low cloudiness. Stratus fractus and Cumulonimbus capillatus were most frequently observed during total and high cloudiness on the low-level. In the warm season and the daytime, clouds are more isolated; in the cool season, they form more dense cloud layers.